PERENCANAAN ARSITEKTUR ENTERPRISE DENGAN METODE TOGAF VERSI 9 (STUDI KASUS: RUMAH SAKIT UMUM KOTA TANGERANG SELATAN) - Cahamalda Vangoslava; Zulfiandri Zulfiandri; M. Nur Gunawan (STUDIA INFORMATIKA: JURNAL SISTEM INFORMASI, 2017)
General Hospital (RSU) South Tangerang City is a health service under the Health Office of Tangerang Selatan City Government that organizes individual health services and provides various health services such as outpatient, inpatient, and emergency room (IGD). In carrying out health service activities, South Tangerang City Public Hospital has not used SI/IT in its entirety to support its operational activities, so the cause of health services to patients becomes obstructed. Some other problems that have not existed between the system, the information is not complete and the previous development is done only based on the time that the system is built overlap. Hospitals need labor. Enterprise architecture planning in this research using TOGAF (The Open Group Architecture Framework) version 9 with ADM (Architecture Development Method) method. This enterprise architecture design generates blueprint targets for business architecture, archival data, architectural applications, technology architectures, gap analyzes, and application implementation roadmaps. From this research, it is expected that South Tangerang City Public Hospital can be built with blueprint architectural concept which has been prepared in accordance with mission and organizational purpose to improve the qualityof health service for the community.